Mixed convection flow in a lid-driven enclosure filled with a fluid-saturated porous medium - Khanafer, Khalil M.; Chamkha, Ali J. (International journal of heat and mass transfer, 1999)
Volume averaged equations governing unsteady, laminar, mixed convection flow in an enclosure filled with a Darcian fluid-saturated uniform porous medium in the presence of internal heat generation is formulated. The two vertical walls of the enclosure are insulated while the horizontal walls are kept at constant temperatures with the top surface is moving at a constant speed. The developed equations are nondimensionalized and then solved numerically subject the appropriate initial and boundary conditions by the finite-volume approach along with the Alternating Direct Implicit (ADI) procedure. Comparisons with previously published work are performed and found to be in excellent agreement. A parametric study is conducted and a set of graphical results is presented and discussed to elucidate interesting features of the solution.